Managing dual business models in emerging markets: an ambidexterity perspective. (1st August 2015) - Winterhalter, Stephan; Zeschky, Marco B.; Gassmann, Oliver
Abstract : Research on dual business models has highlighted the challenge for firms when they compete with different business models in a market. Drawing from ambidexterity literature, we investigate the question of how firms integrate or separate business models at the level of value chain activities, which constitute the core operational activities within each business model. We employ a qualitative research approach based on 11 case studies of Western firms that implemented a low‐cost business model in parallel to their premium business model in emerging markets. We find that firms may become ambidextrous in their business models by means of domain separation. In doing so, firms may separate value chain activities to address different additional customer segments in emerging markets. This study contributes to the emerging topic of dual business models and provides the ground for future research on ambidexterity in a global context.